Tourism and hospitality internships: a prologue to career intentions? - Farmaki, Anna (My University, 2018)
Despite their assumed benefits, negative internship experiences have been reported amongst tourism and hospitality students, which in turn minimise the likelihood of pursuing a career in the industry. This study explores the influence of internship experiences on the career intentions of tourism and hospitality management students. Drawing upon qualitative data, the article highlights the multi-faceted and complex nature of graduates’ career decision-making and reveals that an interplay of factors influences the relationship between internship experiences and students’ career intentions. Important insights are offered that contribute to the understanding of aspects relevant to internships’ efficient design and informed management.
Keywords: Career intentions; Hospitality; Internships; Tourism